Exploring teachers’ technology adoption: linking TPACK knowledge and UTAUT-3 constructs - Rodnie Kgalemelo Mafa; Desmond Wesley Govender (Discover Education)
Abstract For a number of years now, the use of information and communication technology (ICT) in the education sector has grown significantly. The purpose of this study was to evaluate the relationships between teachers' perceived usage of technology and the knowledge domains from the Technological Pedagogical and Content Knowledge (TPACK) framework and the Universal Theory of Acceptance of Use of Technology (UTAUT-3) framework's constructs. This study used a quantitative research design. Participants in this study included in-service educators from both public and private secondary schools in Botswana. The results of this study demonstrated relationships between the UTAUT-3 components and the knowledge domains of TPACK teachers. There were favourable relationships between Performance Expectancy (PE) from UTAUT-3 and Technological Content Knowledge (PCK), Pedagogical Knowledge (PK), Content Knowledge (CK), and Pedagogical Content Knowledge (PCK), technological content knowledge (TPCK), technological pedagogical knowledge (TPK), and CK. The findings also demonstrated that teachers' use and integration of technology in teaching and learning, as well as their behavioural intention to use it, were positively impacted, if weakly, by perceived ease of use as measured by Effort Expectancy (EE).